Using family history information to promote healthy lifestyles and prevent diseases; a discussion of the evidence - Yoon Paula W; Walter Fiona M; Qureshi Nadeem; Wijdenes-Pijl Miranda; Janssens A Cecile JW; Henneman Lidewij; Claassen Liesbeth; Timmermans Danielle RM (BMC, 2010)
Abstract Background A family history, reflecting genetic susceptibility as well as shared environmental and behavioral factors, is an important risk factor for common chronic multifactorial diseases such as cardiovascular diseases, type 2 diabetes and many cancers. Discussion The purpose of the present paper is to discuss the evidence for the use of family history as a tool for primary prevention of common chronic diseases, in particular for tailored interventions aimed at promoting healthy lifestyles. The following questions are addressed: (1) What is the value of family history information as a determinant of personal disease risk?; (2)How can family history information be used to motivate at-risk individuals to adopt and maintain healthy lifestyles in order to prevent disease?; and (3) What additional studies are needed to assess the potential value of family history information as a tool to promote a healthy lifestyle? Summary In addition to risk assessment, family history information can be used to personalize health messages, which are potentially more effective in promoting healthy lifestyles than standardized health messages. More research is needed on the evidence for the effectiveness of such a tool.